Preliminary morphological studies on the effect of substitution in yttrium iron garnet system - See, Alex; Yahya, Noorhana; Hashim, Mansor (Universiti Putra Malaysia Press, 2005)
This is a preliminary study on the phase and morphology of La-subtitution in Y3.0-XLaXFe5O12 prepared via conventional method with x = 0.0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0. The Y3.0-XLaXFe5O12 series were sintered at 1300°c for 10 hours. XRD studies confirmed the garnet phase of all the samples. Particle size distribution was done to study the effect of Lanthanum on the effect of the sample powder. From the result of this work, SEM analysis, the Y2.5La0.5Fe5O12 has the largest grain size (4.146). In conclusion, Lanthanum helps in constituting smaller grain size (1.852 μm) and better magnetic properties.